Non-dispersive ultra-violet spectroscopic detection of formaldehyde gas for indoor environments - Davenport, J. J.; Hodgkinson, Jane; Saffell, J. R.; Tatam, Ralph P. (IEEE, 2018)
We describe a simple method for detecting formaldehyde using low resolution non-dispersive UV absorption spectroscopy. A two channel sensor was developed, making use of a strong absorption peak at 339 nm and a neighbouring region of negligible absorption at 336 nm as a reference. Using a modulated UV LED as a light source and narrow laser-line filters to select the desired spectral bands, a simple detection system was constructed specifically targeted at formaldehyde. By paying particular attention to sources of noise, a minimum detectable absorbance of 5×10 -5 AU was demonstrated with a 20 s averaging period (as ΔI/I0). The system was tested with formaldehyde finding a limit of detection of 4.3 ppm for a 195 mm gas cell. As a consequence of the low gas flow rates used in our test system, a time period of over 8 min was used in further tests, which increased the minimum detectable absorbance to 2×10 -4 AU, 17 ppm of formaldehyde. The increase was the result of thermal drift caused by unwanted temperature variation of the UV LED and the filters, resulting in a zero uncertainty estimated at 560 ppm °C -1 and 100ppm °C -1 respectively.
Keywords: gas detectors; light emitting diodes; optical sensors; pollution measurement; spectroscopy; ultraviolet sources